Kajian Teologis Pandangan Multikultural Dari Prespektif Pendidikan Agama Kristen Tentang Multikultural - Doni. A; Dyulius Thomas Bilo (Sinar Kasih: Jurnal Pendidikan Agama dan Filsafat, 2023)
In a multicultural life, Indonesia has very unique differences, both in terms of culture, customs, ethnicity, religion and language. It can be illustrated that culture can be viewed as a basis for behavior in the world to live in diversity. The existence of cultural diversity in Indonesia is unique and at the same time there is a national opportunity, besides that it can also play a role as a factor of unrest in various regions in a democracy. So in writing this article the author will examine the multicultural view Tologically from the perspective of Christian Religious education regarding multiculturalism, to be used as one of the solutions to minimize conflicts that often occur both in terms of culture, customs, ethnicity and language, which is centered on teaching the Bible, especially for PAK teachers to apply to pupils or students. In this article the author also uses qualitative methods to get the right sources to develop hypotheses related to the topic or topic of research. A proper qualitative approach involves analysis and description of all sources, information, and data in the literature. Qualitative research is information based on sources from various sources, both literature and other sources. Relevant data, number theory, scientific journals and other relevant literature.